LAW ENFORCEMENT EFFORTS AGAINST TRAFFIC ACCIDENT CRIMES LINKED TO LAW OF THE REPUBLIC OF INDONESIA NUMBER 22 OF 2009 CONCERNING TRAFFIC AND ROAD TRANSPORTATION - Ranisya Hadi, Vira; Guntara, Deny; Abas, Muhamad (Jurnal Ilmiah Advokasi, 2025)
To encourage economic development, technological progress, local government, state formation, administrative responsibility, and the safe and effective transportation of people and goods across the country, the federal government must fulfill its commitment to a highly developed transportation infrastructure. The purpose of this is to learn about incidents involving vehicles and seek efforts from law enforcement and the public to reduce the number of traffic accidents. Empirical Juridical Methodology is used in this research process and research specifications use analytical descriptive. The results of the research from the first problem formulation are, as a preventive measure, increasing supervision of road traffic and transportation such as facilities and infrastructure, infrastructure, and vehicle safety on the road and secondly, based on the law, criminal accidents are an incident caused by unintentional, negligent and careless driving by a perpetrator. The author concludes that in efforts to enforce traffic laws, there needs to be awareness and an important role for the government, as well as law enforcers, to participate in encouraging the public to be more aware when driving and pay attention to whether vehicles are suitable for use or not. For perpetrators of traffic accident offenses there are sanctions that apply through Article 310, but in general in traffic accident cases the Restorative Justice method is often used because the incident is an Ordinary Offense. Keywords: Transportation; Traffic; Road Transport; Security.